Tax bracket creep and its effects on income distribution - Burkhard Heer; Bernd Süssmuth (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2013)
We quantitatively analyze the way inflation alters the inequality of the income distribution in the U.S. economy. The main mechanism emphasized in this paper is the bracket creep effect according to which inflation pushes income into higher tax brackets. Governments adjust the nominal income tax brackets slowly and incompletely due to the rise in prices. In the U.S. postwar history, this typically happens less often than once every other tax year. In the first part of the paper, we study time series from the U.S. economy. As our central result we find that irrespective of the level of inflation more frequent income tax schedule adjustments make the relationship between inflation and income inequality more transitory in nature. In the second part of the paper, we develop a general equilibrium monetary model with income heterogeneity that is in line with our time series evidence. We find that a longer duration between two successive adjustments of the tax schedule reduces employment, savings, and output.
Keywords: D31; E31; E44; E52; E62; 330; Bracket Creep; Progressive Income Taxation; Inflation; Income Distribution